Inelastic responses of swollen nitrile rubber under cyclic loading - Loo, Mei Sze; Le Cam, Jean Benoît; Andriyana, Andri; Robin, Eric (American Chemical Society, 2018)
Palm biodiesel is deemed a promising future fuel substitute for conventional diesel fuel. In line with this perspective, necessary changes in the existing diesel engine system are expected in order to address the issue of material compatibility. One typical degradation observed in rubber components exposed to aggressive solvent such as palm biodiesel during the service is swelling. Thus, the investigation of the effect of swelling on the mechanical response under cyclic loading is prerequisite for durability analysis of such components. In this study, filled and unfilled swollen nitrile rubbers are immersed in conventional diesel and palm biodiesel baths until a 5% swelling level is achieved. Both dry and swollen rubbers are subjected to uniaxial cyclic loading tests. The analysis of the mechanical responses has shown that swelling decreases inelastic effects such as hysteresis, stress softening, and permanent set. For both dry and swollen rubbers, fillers are found to have significant effects in the inelastic responses, whereas the effects of solvent and loading rate are comparable.